Candida Flora Colonization And Its Complications In Patients With Down Syndrome - Mehrdad Asadi; Hossein Nowrozi; Abdulhasan Kazemi; Mehraban Flahati; Ali Kazemi; Mohammad Adibpour; Khosro Sedigh Bayan; Seyed Amir Yazdanparast (Tehran University of Medical Sciences, 2012)
Background and Aim: Candida spp can colonize in oral cavity in immunocompromised patients and can lead to candidiasis. Because of immunocompromised condition in patients with Down syndrome, this study aimed at the colonization rate of candida spp in the mouths of such patients. Materials and Methods: This descriptive cross-sectional study was carried out on 53 patients with Down syndrome (29 males and 24 females) within the age range of 4-31 years (mean age: 11.1 years) and supported by the welfare organization, Tabriz branch. The samples were taken from the dorsal and buccal parts of tongues using sterile swabs, and were cultured on Sabouraud Dextrose Agar (SDA+ Chloramphenicol) and corm candida agar. Determination of candida species was based on phenotype characteristics and chlamydoconidia production in Corn Meal Agar containing Tween 80. Results: Altogether 60 isolates of candida spp were isolated from 46 positive patients [26 males (56.52%) and 20 females (43.48%)]. C.albicans with 35 cases (66.03%) were the most frequent isolate and C.dubliniensis with 9 cases (16.98%), C.krusei with 7 cases (13.20%), C.globrata with 5 cases (9.43%) and C.tropicalis with 4 cases (7.54%) were the following ranks. In 12 patients (22.4%), there were more than one species of candida in their oral cavity. Conclusion: Due to the immunocompromised condition in patients with Down syndrome caused by a decrease in IgA and the activity of H2O2 (main destructive agent of C.albicans), the necessity of colonization rate of Candida in such patients is recommended.